Influence of primary hypogenous seeds of phaseolus coccineus in cucurbitacin-containing phytonematicides on plant growth and namatode suppression - Ramoetlo, Motsatsi Priscilla (My University, 2022)
Runner beans are extremely sensitive to root-knot (Meloidogyne species) nematodes. Phytonematicides had been consistently used in managing population densities of Meloidogyne species in various crops, with the application technologies being restricted to the ground leaching technology (GLT) and botinemagation technology, each with its own advantages and disadvantages. The use of seeds as carriers of active ingredients of phytonematicides and then drying prior to sowing, is being considered as another potential application strategy in seeds with hypogeal germination. In such seeds, during seedling emergence the seed cover and the endosperm remain below the soil surface, just above the developing root system. As a result, in phytonematicide-primed seeds, the seed structures could serve as carriers for the active ingredients of phytonematicides. In cucurbitacin phytonematicides, Nemarioc-AL and Nemafric-BL phytonematicides contain cucurbitacin A and B, respectively as active ingredients. The objectives of the study were two-fold, namely, to determine whether runner bean (Phaseolus coccineus L.) seeds would (1) serve as carriers of active ingredients of cucurbitacin-containing phytonematicides without affecting seed germination under in vitro conditions, (2) serve as carriers of cucurbitacins intended for suppression of M. incognita population densities under greenhouse and microplot conditions. Two separate studies were conducted under laboratory conditions, with seven treatment solutions at 0, 2, 4, 8, 16, 32 and 64% Nemafric-BL or Nemarioc-AL phytonematicide. After exposure to separate solutions for 2 h, runner bean seeds were dried on laboratory benches for 72 h. Treatments were arranged in a completely randomised design (CRD), with 8 replications. Two layers of filter papers were placed inside each Petri dish seeded with 10 primed and dried seeds. Petri dishes were incubated inside LABCON growth chamber at 25ºC and 75% relative humidity. Successful seed germination, viewed as emergence of radicle from the testa, was recorded daily for a period of 10 days, with each count being removed from Petri dish to avoid re-counting. Under greenhouse and microplot conditions, primed-and dried seeds were sown in plastic pots containing 2 700 ml steam-pasteurised sandy loam soil, arranged in a randomised complete block design, replicated six times and eight times, respectively. Each seedling was inoculated by distributing 5 000 eggs and second-stage juveniles (J2) of M. incognita race 4 using a 50 ml plastic syringe. Originally, pots were irrigated using 500 ml chlorine-free tapwater, which was reduced to half after seedling emergence at every other day. Plant variables were collected at 56 days after inoculation and data were subjected to the Curve-fitting Allelochemical Response Dose algorithm model. In vitro, germination percentage (R 2 = 0.96), radicle length (R 2 = 0.89) and plumule diameter (R 2 = 0.96) versus Nemarioc-AL phytonematicide exhibited positive quadratic relations. Similarly, the variables versus Nemafric-BL phytonematicide, exhibited positive quadratic relations. In vitro, Mean Concentration Stimulation Point (MCSP) value of Nemarioc-AL phytonematicide on runner bean seeds was 1.05%, whereas for Nemafric-BL phytonematicide MCSP value was 0.58%. Under greenhouse conditions, plant height (R 2 = 0.97), chlorophyll content (R 2 = 0.92), dry shoot mass (R 2 = 0.98), dead nodule number (R 2 = 0.90), total pod number (R 2 = 0.97) and active nodule number (R 2 = 0.93) versus Nemarioc-AL phytonematicide exhibited positive quadratic relations., Similarly, chlorophyll content (R 2 = 0.95), gall rating (R 2 = 0.82), dry shoot weight (R 2 = 0.69), stem diameter (R 2 = 0.85) and total nodule number (R 2 = 0.86) versus Nemafric-BL phytonematicide exhibited positive quadratic relations. Under greenhouse conditions, MCSP values for Nemarioc-AL and Nemafric-BL phytonematicides were 4.18 and 3.69%, respectively. Under microplot conditions, total number of nodules (R 2 = 0.88), number of nodules dead (R 2 = 0.99), number of nodules active (R 2 = 0.95), fresh root mass (R 2 = 0.99), and fresh pod mass (R 2 = 0.99) versus Nemarioc-AL phytonematicide, exhibited positive quadratic relations, whereas plant height (R 2 = 0.85), number of nodules dead (R 2 = 0.87), dry shoot mass (R 2 = 0.97), fresh root mass (R 2 = 0.97) and total number of nodules (R 2 = 0.63) versus Nemafric-BL phytonematicide exhibited positive quadratic relations. Under microplot conditions, MCSP values for Nemarioc-AL and Nemafric-BL phytonematicides were 3.76 and 3.93%, respectively, each with ∑k = 0. All degrees of Nemarioc-AL and Nemafric-BL phytonematicides profoundly reduced nematode numbers under greenhouse and microplot trials. Based on the information obtained from this study, it was confirmed that runner bean (P. coccineus) is sensitive to Nemafric-BL and Nemarioc-AL phytonematicides supported by the Curve-fitting Allelochemical Response Dose (CARD) model results due to most plant variables that had sensitivity values of zero. In conclusion, the priming technology should be developed further since it has the potential of being successful in nematode management in seeds with hypogeal germination
Thesis (M.Sc.(Plant Protection)) -- University of Limpopo, 2022
Keywords: Runner beans; Nematodes; Meloidogyne; Phytonematicides; Growth (Plants); Nematode diseases of plants; Plants -- Development; Scarlet runner bean